2013
DOI: 10.5006/0739
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of API 5L X65 Carbon Steel Under Supercritical and Liquid Carbon Dioxide Phases in the Presence of Water and Sulfur Dioxide

Abstract: Depending on the capture process, liquid or supercritical carbon dioxide (CO 2) can contain impurities like water (H 2 O) and sulfur dioxide (SO 2), increasing the likelihood of corrosion of carbon steel pipelines even if there is no free water in the system. To understand the corrosion risk for such pipelines, the present study focused on the effects of CO 2 phase change, water, and SO 2. Different CO 2 phases (liquid and supercritical) and concentrations of SO 2 (<1%) were simulated in an autoclave-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…[4] This observation is attributed to the ability of O2 to react with SO2 and water to produce sulphuric acid (H2SO4), as will be discussed later. [27] and Farelas et al [86] could be regarded as being very high when compared with the proposed impurity limits outlined by the DYNAMIS project and Alstom in Table 4, which suggest a lower limit of 100 ppm.…”
Section: Anticipated Corrosion Rates In Co2-h2o-so2-o2 Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] This observation is attributed to the ability of O2 to react with SO2 and water to produce sulphuric acid (H2SO4), as will be discussed later. [27] and Farelas et al [86] could be regarded as being very high when compared with the proposed impurity limits outlined by the DYNAMIS project and Alstom in Table 4, which suggest a lower limit of 100 ppm.…”
Section: Anticipated Corrosion Rates In Co2-h2o-so2-o2 Environmentsmentioning
confidence: 99%
“…Investigators have shown that increasing SO2 concentration in dense phase CO2 results in an increase in general corrosion rate [4,83,86] and can also promote localised corrosion under FeSO3/FeSO4 deposits. [76] Some authors have also demonstrated a noticeable synergy existing between SO2 and O2 which results in the synergistic corrosion rate being greater than the sum of the individual corrosion rates from the presence of SO2 and O2 individually.…”
Section: Anticipated Corrosion Rates In Co2-h2o-so2-o2 Environmentsmentioning
confidence: 99%
“…Both the work presented in this publication and the results of Farelas et. al., 12 indicate that mass loss results can be misrepresentative in terms of the threat posed to carbon steel exposed to impurity containing dense phase CO 2 .…”
Section: Corrosion Product Morphology and Compositionmentioning
confidence: 99%
“…These results, to a certain extent, are in alignment with the observation of Farelas et. al., 12 who performed experiments in liquid CO 2 at 25°C and 8 MPa in under-saturated containing 650 ppm water and identified that localized corrosion rates are significant in such systems. Mass loss measurements after 24 hours of exposure revealed general corrosion rates of 0 and 0.1 mm/year in the presence of 0.05 and 0.1% SO 2 , respectively.…”
Section: Corrosion Product Morphology and Compositionmentioning
confidence: 99%
“…The distribution of these components between the aqueous (brine) and CO 2 -rich phase and the interplay between solvation and confinement phenomena at solid-fluid interfaces are complex coupled processes [37]. Some aspects of the reactivity of acid gases have been investigated, such as alteration of well-bore cements by brines containing significant amounts of CO 2 and H 2 S [38,39] and corrosion of steel by CO 2 containing H 2 O and SO 2 [40]. However, current experimental data and molecularlevel simulations of these multi-component systems are insufficient for predicting fluidrock interactions in the bulk and confined CO 2 -rich phase.…”
Section: Acids In Binary and Multi-component Co 2 -Rich Fluidsmentioning
confidence: 99%